FACTORS AFFECTING THE INTEGRITY OF FINANCIAL STATEMENTS ON INDONESIAN SHARIA COMMERCIAL BANKS - Wardani, Cindi Kurnia; laili, Nur; Rifan, Dinda Fali (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to determine the influence of Islamic corporate governance and company size on the integrity of financial statements in Indonesian Islamic commercial banks in 2020-2023. This study uses quantitative research. The kind of data used in this study is secondary data obtained from data on good corporate governance reports and annual reports of Indonesian Sharia commercial banks registered with the Financial Services Authority in 2020-2023. The data collection techniques in this study are documentation and literature studies. The data analysis method used is multiple linear regression using the IBM SPSS Version 25 tool. The results of this study show that Islamic corporate governance does not affect the integrity of financial statements. The size of the company does not affect the integrity of the financial statements. Islamic corporate governance and company size simultaneously do not affect the integrity of financial statements. Islamic corporate governance must be carried out in accordance with Sharia principles as stated in the Qur'an surah Al-Baqarah verse 282. Allah commands that every business activity be carried out with transparency and accountability.